High-resolution 3T-MRI with microcoil enhancement for preoperative evaluation of cutaneous squamous cell carcinoma: a case report and literature review - Cao, Shun; Zhan, Shaowei; Tang, Mengxiao; Yu, Qiuyu; Hu, Hongjie (Frontiers in Medicine, 2026)
BackgroundCutaneous squamous cell carcinoma (cSCC) is a common non-melanoma skin cancer with potential for local invasion and metastasis. Accurate preoperative assessment is essential for optimal treatment planning.Materials and methodsWe report a case of an 83-year-old female patient who presented with a progressively enlarging scalp mass over 3 months. HR-MRI revealed a mixed-signal lesion (22 × 15 × 26 mm) in the right scalp. On T1-weighted imaging (T1WI) and T2-weighted imaging (T2WI), the lesion exhibited heterogeneous signals with an irregular, crater-like surface. Post-contrast imaging demonstrated significant heterogeneous enhancement. The tumor was located within the epidermis, dermis, and subcutaneous fat, closely adhering to the galea aponeurotica with well-defined margins. Surgical resection and histopathological examination confirmed a (exophytic type) moderately to well-differentiated cSCC (2.8 × 2.3 × 2.0 cm) infiltrating the subcutaneous tissue but without perineural invasion or deeper tissue involvement.ResultsHR-MRI provided clear visualization of tumor morphology, infiltration depth, and relationship with surrounding structures. Compared to conventional MRI, HR-MRI improved the accuracy of tumor boundary delineation, offering valuable information for preoperative planning.ConclusionHR-MRI plays a significant role in the evaluation of cSCC, particularly in assessing tumor infiltration depth and differentiating it from other cutaneous malignancies. Its high-resolution imaging facilitates early detection, precise surgical planning, and improved patient outcomes.